Just like Jesus - Lucado, Max.; Hall, Monica (Nashville, Tenn. : T. Nelson, 2003)
A collection of stories of everyday life, with commentary, designed to help one develop a forgiving heart, a willing heart, an enduring heart, and otherwise become more like Jesus.
Keywords: Christian teenagers -- Religious life -- Juvenile literature; Teenagers -- Religious life; Christian life; Conduct of life